Exposure to early childhood development interventions and its association with responsive feeding and nutritional status of 6 to 35 months old children - Jarole, Swati; Gupta, Subodh S.; Mehendale, Ashok M.; Raut, Abhishek (International Journal Of Community Medicine And Public Health, 2019)
Background: The objective of the study was to study the association between exposure to early childhood development (ECD) interventions and responsive feeding and nutritional status among 6-35 months’ children. Methods: The present analytical cross-sectional study was conducted with 360 children from a primary health centre (PHC) area under the ECD project and 360 children from comparison PHC area. The anthropometric measurement and responsive feeding was assessed and compared among 6-35 months’ children. Results: There was significant difference in mean scores of ECD activity (p=0.001) and responsive feeding (p<0.001) in ECD area as to comparison area. In the ECD program area, the proportion of children who were malnourished (33.3%) were less as compared to control area (53.9%). Conclusions: The present study shows ECD interventions at community level delivered through frontline workers resulted in improved responsive feeding practices better nutritional outcomes for children.